Toll-like receptor 4 is required for α-synuclein dependent activation of microglia and astroglia - Fellner, Lisa (Wiley Subscription Services, Inc., A Wiley Company, 2013)
Alpha-synucleinopathies (ASP) are neurodegenerative disorders, characterized by accumulation of misfolded α-synuclein, selective neuronal loss, and extensive gliosis. It is accepted that microgliosis and astrogliosis contribute to the disease progression in ASP. Toll-like receptors (TLRs) are expressed on cells of the innate immune system, including glia, and TLR4 dysregulation may play a role in ASP pathogenesis. In this study we aimed to define the involvement of TLR4 in microglial and astroglial activation induced by different forms of α-synuclein (full length soluble, fibrillized, and C-terminally truncated). Purified primary wild type (TLR4(+/+)) and TLR4 deficient (TLR4(−/−)) murine microglial and astroglial cell cultures were treated with recombinant α-synuclein and phagocytic activity, NFκB nuclear translocation, cytokine release, and reactive oxygen species (ROS) production were measured. We show that TLR4 mediates α-synuclein-induced microglial phagocytic activity, pro-inflammatory cytokine release, and ROS production. TLR4(−/−) astroglia present a suppressed pro-inflammatory response and decreased ROS production triggered by α-synuclein treatment. However, the uptake of α-synuclein by primary astroglia is not dependent on TLR4 expression. Our results indicate the C-terminally truncated form as the most potent inductor of TLR4-dependent glial activation. The current findings suggest that TLR4 plays a modulatory role on glial pro-inflammatory responses and ROS production triggered by α-synuclein. In contrast to microglia, the uptake of alpha-synuclein by astroglia is not dependent on TLR4. Our data provide novel insights into the mechanisms of α-synuclein-induced microglial and astroglial activation which may have an impact on understanding the pathogenesis of ASP. © 2012 Wiley Periodicals, Inc.